Phatic Particles in the Indonesian Translation of Percy Jackson and The Olympians: The Lightning Thief - Aldilla Tsamara Qanita (Translation and Linguistics (Transling), 2025)
Percy Jackson and The Olympians: The Lightning Thief by Rick Riordan is primarily set in American society and the Gr3ek mythological world. Although it has limited direct correlation with Indonesian society, the novel has gained notable popularity among Indonesian readers. Remarkably, the Indonesian translation introduces linguistic elements that do not exist in the source text, particularly phatic particles such as ‘dong’, ‘deh’, ‘kan’, etc. This study examines how the addition of phatic particles in the Indonesian translation contribute to maintaining natural tone and relatability for Indonesian readers. Using a descriptive and qualitative approach, this study identifies ten types of added phatic particles and evaluates their function and translation strategies and techniques. The analysis reveals the application of domestication, adaptation, modulation, and amplification techniques to align expressions with Indonesian conversational norms. Helper and enlightener strategies are also used to support readers’ comprehension and emotional resonance. The translation choices using phatic particles help readers perceive the cultural and interpersonal contexts while also making necessary adjustments. This study argues that while the addition of phatic particles is part of linguistic compartment, it shows the translator’s cultural awareness of both English and Indonesian languages and her intention to present conversation text with natural tone.